LA SECUENCIA IDEANTE: UN NUEVO TIPO DE TEXTO PERIODÍSTICO SEGÚN LAS ENTREVISTAS CORALES DE MARCA.COM1 - Daniel BARREDO IBÁÑEZ,Martín OLLER ALONSO (Fonseca, Journal of Communication, 2023)
The development of Internet has brought the emergence of new forms of discourse and, therefore, new journalistic forms: new cybergenres (as the coral interviews in MARCA.com), which take advantage of the technical – ideological substrate of the net